PENGARUH FAKTOR EKONOMI SOSIAL TERHADAP USIA SAAT MENIKAH PELAKU PERNIKAHAN USIA DINI PADA PEREMPUAN DI KABUPATEN GIANYAR - Aristyana, Putu Ayu Risma; Widanta, A.A. Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023, 2023)
The purpose of this study was to analyze the simultaneous effect of the respondent's education level, parental education level, premarital pregnancy and parental income on the age at marriage of female early marriage offenders in Gianyar Regency and to analyze the partial effect of respondents' education level, parental education level, premarital pregnancy and parental income on age at marriage for women in Gianyar Regency. The number of samples taken was 100 EFA wives. The data analysis technique used was multiple linear regression analysis. The results showed that 1) Simultaneously the respondent's education level, parental education level, premarital pregnancy and parental income had a significant effect on the age at marriage for women in Gianyar Regency. 2) Partially, the respondent's education level has a positive and significant effect on the age at marriage for women in Gianyar Regency. 3) Partially the level of parental education and parental income has no effect on the age at marriage for women in Gianyar Regency. 4) Female respondents who married for reasons of pre-marital pregnancy were lower than those who married not for reasons of pre-marital pregnancy and the difference was significant.